2019
DOI: 10.1111/1462-2920.14646
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of microbially mediated transformations of Synechococcus‐derived dissolved organic matter as revealed by incubation experiments

Abstract: Summary In this study, we investigated the microbially mediated transformation of labile Synechococcus‐derived DOM to RDOM using a 60‐day experimental incubation system. Three phases of TOC degradation activity (I, II and III) were observed following the addition of Synechococcus‐derived DOM. The phases were characterized by organic carbon consumption rates of 8.77, 1.26 and 0.16 μmol L−1 day−1, respectively. Excitation emission matrix analysis revealed the presence of three FDOM components including tyrosine‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
48
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 64 publications
8
48
2
Order By: Relevance
“…Three fluorescent components were analyzed (supporting information Figure S4). Comparison to previous studies indicated that C1 exhibited fluorescence peak typical of protein‐like (tyrosine‐like) component, and the C2 and C3 are often referred to as humic‐like components (Catalá et al, ; Guo et al, ; Jørgensen et al, ; Zheng et al, ). Trends of these components were monitored during the 110‐day incubation and shown in supporting information Figure S4.…”
Section: Resultsmentioning
confidence: 81%
“…Three fluorescent components were analyzed (supporting information Figure S4). Comparison to previous studies indicated that C1 exhibited fluorescence peak typical of protein‐like (tyrosine‐like) component, and the C2 and C3 are often referred to as humic‐like components (Catalá et al, ; Guo et al, ; Jørgensen et al, ; Zheng et al, ). Trends of these components were monitored during the 110‐day incubation and shown in supporting information Figure S4.…”
Section: Resultsmentioning
confidence: 81%
“…XM-24 was isolated from coastal seawaters nearby Xiamen Island (~24 N,~118 E, China) using SN medium (Waterbury 1986;Zheng et al 2018), and its associated heterotrophic bacteria were self-selected natural assemblages. The XM-24 coculture comprised a pure Synechococcus strain and a heterotrophic bacterial community that primarily consisted of several dominant bacterial species (Zheng et al, 2018(Zheng et al, , 2019. The coculture was incubated at 25 C with 10 μmol photonsÁm −2 Ás −1 irradiation in SN liquid medium for the experiments described here.…”
Section: Synechococcus and Cyanophage Culturesmentioning
confidence: 99%
“…DOM that is released by phytoplankton and further transformed by heterotrophic bacteria affects the molecular composition of environmental DOM pools (Azam et al 1983; Zhao et al 2019; Zheng et al 2019). Further, the chemical composition of DOM produced by different marine phytoplankton taxa (e.g., Prochlorococcus , Synechococcus , Thalassiosira , and Phaeodactylum ) partially reflects their taxonomic origins, wherein closely related phytoplankton species share similar profiles of released DOM (Becker et al 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy between the analyses of unfractionated community structure and DNA-SIP identified DOM incorporators highlights the advantage of using the sensitive SIP technique to identify response of oligotrophs to varying DOM sources and quality. Syn lysate is a mixture of abundant labile and less abundant recalcitrant DOM (Zheng et al, 2019a), therefore 13 C incorporation by both copiotrophs and oligotrophs was possible. For example, members of the Acidobacteria clade, a responding lineage to the Syn lysate treatment has been shown to take up cellulose, a byproduct of cyanobacteria production (Nobles et al, 2001;Eichorst and Kuske, 2012;Zhao et al, 2015).…”
Section: Dom Quality Determined Different 13 C-incorporating Microbiamentioning
confidence: 99%